Nursing experience of a patient undergoing modified radical mastectomy (1例乳腺癌改良根治术患者护理体会) - LI Weijia (李唯佳¹); CAO Jinghong (曹红京²) (Association of Integrative Nursing, 2021)
This paper summarized the nursing experience of a patient undergoing modified radical mastectomy, including nursing evaluation, perioperative nursing, pain management, health education before discharge. Given the influence of modified radical mastectomy on appearance and limb function of patients, it is required to carry out targeted and individualized nursing intervention to relive the negative emotion and improve the treatment adherence. (本文总结了1例乳腺癌改良根治术患者护理体会, 包括护理评估、围术期护理、疼痛护理、出院宣教等。乳腺癌改良根治术会改变患者胸部外形, 影响肢体功能, 造成患者生理和心理上的创伤, 不利于术后康复, 通过有针对性的、个体化的护理干预, 能够有效改善患者负性情绪, 提高治疗依从性。)